PENDIDIKAN KEWIRAUSAHAAN DAN PELATIHAN STRATEGI PEMASARAN PRODUK PADA SANTRI PONDOK PESANTREN QODIRIYAH SULAIMANIAH SINGOSARI KABUPATEN MALANG - Andi Asdani Dani; Yunia Afiatin; Atika Syuliswati; Jaswadi; Mika Marsely (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2022)
The Qodiriyah Sulaimaniah Singosari Islamic Boarding School, Malang Regency is one of the large Islamic boarding schools located in Kreweh Singosari Village, Malang Regency. The existence of this Islamic boarding school makes a high contribution to producing young people who have a deep understanding of the Islamic religion. However, the Qodiriyah Sulaimaniah Singosari Islamic boarding school has a desire to provide more provisions to its students, namely the ability to entrepreneurship so that it can produce prospective entrepreneurs who have a good Islamic education. In addition, the Qodiriyah Sulaimaniah Singosari Islamic boarding school also has a desire to develop small businesses that have been owned in the Islamic boarding school. Therefore, PKM activities are carried out by providing training in the field of entrepreneurship, namely marketing strategy training for students at the Qodiriyah Sulaimaniah Singosari Islamic boarding school. In addition, this PkM activity also provides training on skills to make contemporary food, namely rice bowls which are expected to be useful for use as a product of the Qodiriyah Sulaimaniah Singosari Islamic boarding school. The results of this PKM activity are expected to produce students who have the ability to carry out marketing techniques so as to launch entrepreneurial activities that are carried out.